A sex education program for teachers of preschool children: a quasi-experimental study in Iran - Jeno Martin; Hedyeh Riazi; Armin Firoozi; Maliheh Nasiri (BMC, 2020)
Abstract Background Sex education is an important educational dimension. Together with families, teachers play a significant role in providing sex education to children. However, in most cases, they do not have enough information on this topic. The present study aimed to determine the effects of a preschool sex education program on preschool teachers' knowledge and attitude. Methods In this quasi-experimental study, 80 teachers working at preschools in Tehran, Iran, were randomly allocated to experimental and control groups. The educational program was provided in two 90-min sessions for the experimental group while the control group received no intervention. A self-designed knowledge and attitude questionnaire was completed by both groups before and 1 month after the intervention. This questionnaire evaluated knowledge and attitude in six domains of principles of sex education, sexual identity, stages of development and proper methods of sex education, sex-related questions, masturbation, and sexual abuse. Data were analysed in SPSS 18 using descriptive statistics as well as independent samples t-test, paired-samples t-test, chi-squared test, and ANCOVA at p < 0.05. Results Mean scores of knowledge and attitude in all dimensions showed a significant increase in the experimental group following the educational intervention. However, no difference was observed in the control group. Following the educational intervention, mean scores of teachers' knowledge and attitude in all six domains showed a significant difference with that of the control group (p < 0.001). Conclusions Results revealed that the sex education program can promote the knowledge and attitude of preschool teachers in all domains. Trial registration Iranian Registry of Clinical Trials: IRCT2016122320854N5 . Registered on 9 March 2017. "Retrospectively registered".